PENGARUH RISIKO BISNIS, PERTUMBUHAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP PROFITABILITAS SERTA NILAI PERUSAHAAN MANUFAKTUR - Saraswathi, Ida Ayu Anggawulan; Bagus Wiksuana, I Gst; Rahyuda, Henny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 05.NO.06. TAHUN 2016, 2016)
The purpose of this study was to determine the significance of the effect of business risk, growth and capital structure on profitability and value of the company, either direct influence, indirect and total effect. The population in this study are all companies listed on the Indonesia Stock Exchange during the period 2010-2014 the number of companies 124 companies. Methods of sample selection was conducted using total sample or census. Research hypothesis testing using the technique of path analysis (path analysis). The results showed that: (1) variable business risk, perusaaan growth, capital structure and profitability are directly significant effect on the value of the company, (2) variable business risk, growth and capital structure indirect effect on the value of the company through an intermediary variable profitability.
Keywords: Business Risk, Growth, Capital Structure, Profitability and Company Value